Introduction - Editor-in-Chief (Thai Journal of Rheumatology, 2025)
The Thai Journal of Rheumatology, Volume 2, Issue 3, presents a collection of academic articles in the field of rheumatology. This issue aims to disseminate new knowledge and enhance understanding of essential topics in rheumatology practice. The content includes an original article, “Prevalence of Antinuclear Antibody Positivity in Thai Patients with Rheumatoid Arthritis,” which provides valuable data on ANA prevalence in Thai rheumatoid arthritis patients. A review article on “Advanced Imaging in Gout” offers insights into imaging techniques for diagnosis and disease monitoring. In addition, two noteworthy case reports, “Lichenoid Drug Eruption Induced by Rosuvastatin” and “Cryoglobulinemic Vasculitis with Multisystem Involvement,” highlight rare and challenging conditions. To further engage readers, a Rheumatology Quiz is also included to encourage knowledge review and self-assessment. The editorial board sincerely hopes that this issue will be academically enriching and practically helpful for all readers. We also extend our gratitude to all authors for their valuable contributions in maintaining the quality and relevance of the journal. Editor-in-Chief